Sheelagh Millar. The biosocial survey in Hong Kong. Canberra : Unesco/Unep, Centre for Resources and Environmental Studies : The Australian National University, 1979. 517 p. - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1987)
SHEELAGH MILLAR. The biosocial survey in Hong Kong, UNESCO/UNEP, Centre for Resources and Environmental Studies, The Australian National University, Canberra, 1979.